Gone again (Jack Swyteck novels, 12,, 2016)
Sashi Burgette vanished three years ago. The night after the teenager’s disappearance, ex-con Dylan Kyle was stopped for drunk driving. An article of Sashi’s clothing was found in his truck, and a police videotape of his drunken explanation under interrogation sealed his fate at trial. Now, just days from Kyle’s execution, Sashi’s mother visits Jack Swyteck, doing pro bono work at the Freedom Institute, and delivers shocking news: “Sashi called me.” The police dismiss the call as a cruel hoax. An innocent man may be executed and time is running out—unless his lawyers can locate Sashi. A man of principle who believes in justice, Jack jumps into the investigation.

The tenth justice (Wheeler large print book, ,, 2009)
A lawyer working for a Supreme Court judge makes the mistake of revealing to another lawyer a ruling about to be announced. The other is in fact an impostor and threatens to reveal the indiscretion unless he is paid money. The lawyer and his friends mount an operation to fix the blackmailer. A first novel.

Most dangerous place (Jack Swyteck novels, 13,, 2017)
It begins at the airport, where Jack is waiting to meet his old high school buddy, Keith Ingraham, a high-powered banker based in Hong Kong, coming to Miami for his young daughter's surgery. But their long-awaited reunion is abruptly derailed when the police arrest Keith's wife, Isabelle, in the terminal, accusing her of conspiring to kill the man who raped her in college. Jack quickly agrees to represent Isa but soon discovers that to see justice done, he must separate truth from lies - an undertaking that proves more complicated than the seasoned attorney expects.

The king of torts (Random House Large Print in association with Doubleday, Knopf Doubleday Publishing Group, Findaway World, Random House Large Print, Random House, Books on Tape, Doubleday, Random House Audio, 2007)
Clay Carter, a public defender, reluctantly takes the case of a young man charged with a random street killing, assuming it is just another of the many senseless murders that hit D.C. every week. As he digs into the background of his client, Clay stumbles on a conspiracy too horrible to believe. He suddenly finds himself in the middle of a complex case against one of the largest pharmaceutical companies in the world, looking at the kind of enormous settlement that would totally change his life--that would make him almost overnight, the legal profession's newest king of torts.

The brethren (Island Books, Dell, Knopf Doubleday Publishing Group, Random House Large Print, BDD Audio, Books on Tape, Doubleday, 2008)
They call themselves the Brethren: three disgraced former judges doing time in a federal prison in Florida. Meeting daily, these judges-turned-felons reminisce about old court cases, and contemplate where they went wrong in their lives. They decide to use their jail time in a more profitable manner: devising an extortion scam so perfect that they won't know why it fell apart until it's too late.

The big lie (Jack Swyteck novels, 16,, 2020)
As the Electoral College battle for the White House lands in a Florida courtroom, Miami attorney Jack Swyteck has never felt farther from the truth, fighting for a faithless elector, caught between a corrupt president and his manipulative opponent--with each revelation more explosive than the next. The country is reeling. For the sixth time in American history, the winner of the popular vote will not occupy the Oval Office. President Malcolm MacLeod, the Machiavellian incumbent, was spared from impeachment only because his political foes were certain they would oust him at the ballot box. Now, he appears to have secured a second term, thanks to a narrow victory in the Electoral College. His opponent, Florida Senator Evan Stahl, saw his campaign rocked by allegations of an extramarital affair--with another man. Despite the salacious headline-making scandal and the surrounding media frenzy, most Americans chose Stahl to lead the politically polarized nation. But Stahl is refusing to concede. Backed by millions of supporters, he looks to individual members of the Electoral College to cross party lines. Gun lobbyist Charlotte Holmes is one of Floridas twenty-nine electors who is bound by law and by oath to cast her vote for MacLeod, who won Florida by the thinnest of margins. When Charlotte announces that she intends to vote her conscience and throw the Electoral College to Stahl, the president and his Florida machine haul her into court on felony charges--which, for some, isn't nearly punishment enough. Miami attorney Jack Swyteck is going to use every legal maneuver he can to keep his new client free--and alive. MacLeod's hand-picked prosecutor is determined to prove Charlotte is unfit to cast a vote. Dredging through her past, he's looking for skeletons to humiliate and discredit her, while others with far deadlier intentions have begun acting on their threats. As the pressure mounts, Charlotte and Jack must decide how far they'll go to stand their ground in the stand-your-ground state.--

The litigators (Dell, Knopf Doubleday Publishing Group, Distributed by Recorded Books, [Manufactured and distributed by] Findaway World, LLC, Random House Digital, Playaway Digital Audio, Random House, Inc, Penguin Random House, Random House Large Print, Books on Tape, Doubleday, Random House Audio, 2012)
Law firm partners Oscar Finley and Wally Figg see a chance for huge financial gain when they learn of a pending class action lawsuit against the makers of Krayoxx, a popular cholesterol-reducing drug suspected of causing heart attacks.

The rainmaker (Island Books, Knopf Doubleday Publishing Group, Bantam Audio, Delta Trade Paperbacks, Bantam Doubleday Dell Audio Pub, Random House Digital, Books on Tape, Doubleday, 2008)
Bestselling author John Grisham returns to the courtroom for the first time since A Time to Kill to weave this riveting tale of legal intrigue and corporate greed. Combining suspense, narrative momentum, and humor as only John Grisham can, The Rainmaker provides another spellbinding, thrill-a-minute read.

The summons (Knopf Doubleday Publishing Group, Repackaged and distributed by Taped Editions, Random House Large Print, Distributed by Books on Tape, Bantam Dell, Books on Tape, Doubleday, Random House Audio, 2007)
Ray Atlee is a newly-divorced law professor at the University of Virginia when he and his brother are summoned home to Clanton, Mississippi, by his dying father. Unfortunately, Judge Atlee dies before his sons arrive, leaving the details of his estate unsettled and a secret known only to Ray ... and perhaps someone else. --

In the name of honor (Thorndike Press large print core, ,, 2011)
Capt. Paul Terry, one of the army's most accomplished young lawyers, must defend Brian McCarran, a general's son who recently returned from a harrowing tour in Iraq. In the high-profile court-martial, Terry is joined by Brian's sister, Meg McCarran, who leaves her practice in San Francisco to help save her brother. Before the case is over, Terry will become deeply entwined with Meg and the McCarrans--and learn that families, like war, can break the sturdiest of souls.

Rogue lawyer (Rogue Lawyer, ,, 2016)
Sebastian Rudd is not your typical street lawyer. He works out of a customized bulletproof van, complete with Wi-Fi, a bar, a small fridge, fine leather chairs, a hidden gun compartment, and a heavily armed driver. He has no firm, no partners, no associates, and only one employee, his driver, who's also his bodyguard, law clerk, confidant, and golf caddy. He lives alone in a small but extremely safe penthouse apartment, and his primary piece of furniture is a vintage pool table. He drinks small-batch bourbon and carries a gun. Sebastian defends people other lawyers won't go near: a drug-addled, tattooed kid rumored to be in a satanic cult, who is accused of molesting and murdering two little girls; a vicious crime lord on death row; a homeowner arrested for shooting at a SWAT team that mistakenly invaded his house. Why these clients? Because he believes everyone is entitled to a fair trial, even if he, Sebastian, has to cheat to secure one.

The confession (Dell, Knopf Doubleday Publishing Group, Distributed by Recorded Books, Bantam Books Trade Paperbacks, Playaway Digital Audio, Penguin Random House, Random House Large Print, Books on Tape, Doubleday, Random House Audio, 2012)
For every innocent man sent to prison, there is a guilty one left on the outside. He doesn't understand how the police and prosecutors got the wrong man, and he certainly doesn't care. He just can't believe his good luck. Time passes and he realizes that the mistake will not be corrected: the authorities believe in their case and are determined to get a conviction. He may even watch the trial of the person wrongly accused of his crime. He is relieved when the verdict is guilty. He laughs when the police and prosecutors congratulate themselves. He is content to allow an innocent person to go to prison, to serve hard time, even to be executed. Travis Boyette is such a man. In 1998, in the small East Texas city of Sloan, he abducted, raped, and strangled a popular high school cheerleader. He buried her body so that it would never be found, then watched in amazement as police and prosecutors arrested and convicted Donté Drumm, a local football star, and marched him off to death row. Now nine years have passed. Travis has just been paroled in Kansas for a different crime; Donté is four days away from his execution. Travis suffers from an inoperable brain tumor. For the first time in his miserable life, he decides to do what's right and confess. But how can a guilty man convince lawyers, judges, and politicians that they're about to execute an innocent man?

Gray Mountain: [a novel] (Doubleday Large Print Home Library, ,, 2015)
"The year is 2008 and Samantha Kofer's career at a huge Wall Street law firm is on the fast track -- until the recession hits and she is downsized, furloughed, and escorted out of the building. Samantha, though, is offered an opportunity to work at a legal aid clinic for one year without pay, all for a slim chance of getting rehired. In a matter of days Samantha moves from Manhattan to Brady, Virginia, population 2,200, in the heart of Appalachia, a part of the world she has only read about. Samantha's new job takes her into the murky and dangerous world of coal mining, where laws are often broken, communities are divided, and the land itself is under attack. But some of the locals aren't so thrilled to have a big-city lawyer in town, and within weeks Samantha is engulfed in litigation that turns deadly. Because like most small towns, Brady harbors big secrets that some will kill to conceal."--Back cover.

The runaway jury (BDD Audio, ,, 2012)
He has waited for this moment. He has planned his every move. He has made it onto the jury in the most explosive trial of the century. Now the verdict belongs to him. They are at the center of a multimillion dollar legal hurricane: twelve men and women who have been investigated, watched, manipulated, and harassed by high-priced lawyers and consultants who will stop at nothing to secure a verdict. Now that the jury must make a decision in the most explosive trial of the century, a precedent-setting lawsuit against a giant tobacco company. But only a handful of people know the truth: that this jury has a leader, and the verdict belongs to him. He is known only as Juror #2. But he has a name, a past, and he has planned his every move with the help of a beautiful woman on the outside. Now, while a corporate empire hangs in the balance, while a grieving family waits, and while lawyers are plunged into a battle for their careers, the truth about Juror #2 is about to explode, in a cross fire of greed and corruption-and with justice fighting for its life.

The whistler (The Whistler, ,, 2017)
Lacy Stoltz is an investigator for the Florida Board on Judicial Conduct. She is a lawyer, not a cop, and it is her job to respond to complaints dealing with judicial misconduct. After nine years with the Board, she knows that most problems are caused by incompetence, not corruption. But a corruption case eventually crosses her desk. A previously disbarred lawyer is back in business with a new identity. He now goes by the name Greg Myers, and he claims to know of a Florida judge who has stolen more money than all other crooked judges combined. And not just crooked judges in Florida. All judges, from all states, and throughout U.S. history. What the source of the ill-gotten gains? It seems the judge was secretly involved with the construction of a large casino on Native American land. The Coast Mafia financed the casino and is now helping itself to a sizable skim of each month's cash. The judge is getting a cut and looking the other way. It's a sweet deal: Everyone is making money. But now Greg wants to put a stop to it. His only client is a person who knows the truth and wants to blow the whistle and collect millions under Florida law. Greg files a complaint with the Board on Judicial Conduct, and the case is assigned to Lacy Stoltz, who immediately suspects that this one could be dangerous. Dangerous is one thing. Deadly is something else.

Sycamore row (Jake Brigance novels, 2,, 2014)
In this novel the author takes you back to where it all began in A Time to Kill. Now we return to that famous courthouse in Clanton as Jake Brigance once again finds himself embroiled in a fiercely controversial trial; a trial that will expose old racial tensions and force Ford County to confront its tortured history. Seth Hubbard is a wealthy man dying of lung cancer. He trusts no one. Before he hangs himself from a sycamore tree, Hubbard leaves a new, handwritten, will. It is an act that drags his adult children, his black maid, and Jake into a conflict as riveting and dramatic as the murder trial that made Brigance one of Ford County's most notorious citizens, just three years earlier. The second will raises far more questions than it answers. Why would Hubbard leave nearly all of his fortune to his maid? Had chemotherapy and painkillers affected his ability to think clearly? And what does it all have to do with a piece of land once known as Sycamore Row?

Dead even (Rob Weisbach Books, HarperAudio, Harper Audio, Hachette Audio, HarperCollins, Warner Vision Books, 1998)
A woman DA is instructed to win her case or her husband dies and her husband is instructed to win or his wife dies.

The appeal (Dell, Knopf Doubleday Publishing Group, Listening Library, Delta, Penguin Random House, Random House Large Print, distributed by Recorded Books, Books on Tape, Doubleday, Random House Audio, 2008)
In a crowded courtroom in Mississippi, a jury returns a shocking verdict against a chemical company accused of dumping toxic waste into a small town's water supply, causing the worst "cancer cluster" in history. The company appeals to the Mississippi Supreme Court, whose nine justices will one day either approve the verdict or reverse it.

The broker (Knopf Doubleday Publishing Group, Delta Trade Paperbacks, Findaway World, Random House Large Print, Bantam Dell, Findaway World, LLC, Random House, Books on Tape, Doubleday, Random House Audio, 2007)
John Grisham, delivers another legal thriller of unparalled suspense. With fourteen years left on a twenty-year sentence, notorious Washington power broker, Joel Blackman, receives a surprise pardon from a lame-duck president. He is smuggled out of the country on a military cargo plane, given a new identity, and tucked away in a small town in Italy. But Blackman has serious enemies from his past. As the CIA watches him closely, the question is not whether he will be killed, but rather who will kill him first.

The client (Knopf Doubleday Publishing Group, Delta Trade Paperbacks, Random House Digital, Bantam Dell, Bantam Doubleday Dell Audio, Books on Tape, Island, Doubleday, 2008)
" ... Eleven-year-old Mark Sway and his younger brother ... chance encounter with a suicidal lawyer left Mark knowing a bloody and explosive secret: the whereabouts of the most sought-after dead body in America."--colophon.